2018
DOI: 10.1002/jso.25121
|View full text |Cite
|
Sign up to set email alerts
|

High cyclin A expression, but not Ki67, is associated with early recurrence in desmoid tumors

Abstract: Our study indicates that cyclin A may be a new prognostic biomarker in surgically treated desmoid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
(67 reference statements)
0
9
1
Order By: Relevance
“…The biological rationale for an association between high ERβ and high risk of recurrence may be the positive correlation between ERβ and proliferation found in the present study. Our previous observation was that high proliferation is associated with a higher recurrence risk . We found no indication of a linear association between cyclin D1 expression and TTR, although cyclin D1 expression was also associated with higher proliferation rate measured by the expression of Ki67 and cyclin A.…”
Section: Discussioncontrasting
confidence: 72%
See 4 more Smart Citations
“…The biological rationale for an association between high ERβ and high risk of recurrence may be the positive correlation between ERβ and proliferation found in the present study. Our previous observation was that high proliferation is associated with a higher recurrence risk . We found no indication of a linear association between cyclin D1 expression and TTR, although cyclin D1 expression was also associated with higher proliferation rate measured by the expression of Ki67 and cyclin A.…”
Section: Discussioncontrasting
confidence: 72%
“…Our previous observation was that high proliferation is associated with a higher recurrence risk. 14 Despite the documented hormonal dependence of desmoid tumors, expression of ERα has been negative in the vast majority of studies. 3,15 An earlier report suggested that ERα antibody crosslinkage with ERβ may have elicited a few positive ERα findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations